Assessment of thermal heat requirement, radiation energy, water use efficiency, and yield of mango cv Dashehari using fertigation method - TARUN ADAK; KAILASH KUMAR; VINOD KUMAR SINGH (Journal of Agrometeorology, 2017)
Thermal heat requirement as well as energy components depend on weather parameters. Critical phenological stages was taken into consideration for the thermal heat requirement during 2013-15 under fertigation treatment (25, 50 and 75 per cent of recommended fertilizer dose) in mango cv Dashehari at Lucknow region. Mango productivity varied from 4.54-11.84 t ha-1 across different fertigation regimes as a result of differential thermal heat accumulation. In the treatment 25 per cent RDF, productivity of 5.23, 11.13 and 6.12 t ha-1 was recorded during 2013, 2014 and 2015 while in 50 per cent RDF, 6.23, 11.84 and 7.76 t ha-1 was observed. The maximum yield reduction (37.5, 14 and 26.1%) was found in control plot. A significant variation in radiation energy received during the field experiment was revealed and a range of 8.97 to 16.27 mm day-1 extraterrestrial radiation was observed at different critical phenological stages. The heat use efficiency (HUE) varied between 2.54-6.78 g m-2°Cd-1 across seasons and treatments. Water use efficiency (WUE) of 10.8, 14.1, 13.5 and 11.7 kg fruits m-3 was recorded in different fertigated treatments. The highest reduction in WUE was noted in control (23.9%) followed by 17.2 and 4.8% in 25 and 50 per cent as compared to 75 per cent fertigation regimes.